The evaluation of Fourier transform infrared (FT-IR) spectroscopy and multivariate data analysis techniques for quality control at aniIndustrial cellar - Hoon, Ansunette (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.